Evidencia de diferenciación sexual en la almeja Ameghinomya antiqua de la costa chilena y su proporción de sexos - Prida, Valentina; Valenzuela, Andrea; Astorga, Marcela P. (Revista de Biología Marina y Oceanografía, 2019)
Ameghinomya antiqua is one of the most exploited bivalves in Chile, however, the limited information available on its reproductive biology does not allow proper fishery management decisions to be made. The presence of sexual dimorphism and the sex ratios for this species were detected by observation of gonads extracted from specimens collected from Carelmapu and Quellón, southern Chile. One group of specimens showed milky-white gonads with oocytes (females) while the other exhibited orange gonads with spermatocytes (males). The sex ratio obtained in Carelmapu was 1:1.1, with 48.5% males and 51.5% females; in Quellón, the sex ratio was 1:1.01, with 49.77% males and 50.23% females. We found that dimorphism can be assessed by rapid visual observation of the gonads. Our study proposes an easier and faster way of identifying gender in Ameghinomya antiqua, allowing proper monitoring.